Pengukuran Kinerja Pemeliharaan Mesin Produksi Pabrik Kelapa Sawit Menggunakan Overall Equipment Effectiveness (OEE) - M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
Equipment performance of a POM can be measured using OEE. Measurement of OEE on screw press can be done through the operating hours of the equipment and the resulting oil losses. The result of the measurement will show how effectivity the treatment carried out on the equipment. The purpose of this research was to determine the condition of performance of screw press through OEE measurement and to know what indications are shown by the performance condition. This research was conducted at a POM located in South Kalimantan Province. The data used is data derived from company document for one year. Based on the result of the discussion it can be concluded that screw press tool used in POM has low performance condition. This can be seen from the measured OEE value which is still below the world class company standard. The low OEE value indicates that the maintenance system applied to the screw press has not been effective. Therefore it is necessary to do an analysis of causes of the problem so that appropriate repair can be made according to their need